The genetic integrity of bacterial species: the core genome and the accessory genome, two different stories - Segerman, Bo (Frontiers in Cellular and Infection Microbiology, 2012)
Strains within a bacterial species typically have a set of conserved core genes and a variable set of accessory genes. The accessory genes often appear to move laterally between strains, thereby forming new trait combinations. Sometimes, genetic material also moves laterally between species, thereby resulting in diffuse borders between them. The growing number of genome sequences offers new possibilities to study these processes. Ten species for which abundant genomic data exists were here selected for analysis of the species border integrity. The average core genome similarities and relative core genome sizes were determined for strain pairs within the species and for strain pairs crossing the species border. The variability within the species as well as the border integrity varies for different bacterial species. Some have very distinct borders while other are more or less indefinable. From the growing amount of genomic data, it becomes even clearer that the concept of bacterial species is, in many cases, far from absolute.